A modified lithium-rich manganese-based positive electrode material and preparation method thereof, and a battery

By doping K elements and covering TiO2 layers into the lithium-rich manganese-based positive electrode material, the lack of performance of the material in terms of fast capacity attenuation, poor rate performance and cyclic voltage attenuation is solved, and a significant electrochemical performance improvement is achieved.

CN119764395APending Publication Date: 2025-04-04湖北金泉新材料有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411958297.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing lithium-rich manganese-based cathode materials have insufficient performance in terms of fast capacity attenuation, poor rate performance and cyclic voltage attenuation, which cannot meet the needs of practical applications.

Method used

By doping K elements and coating the TiO2 layer, a modified lithium-rich manganese-based positive electrode material is formed. Doping of K element improves the diffusion rate and activity space of lithium ions, while the TiO2 cladding enhances the structural stability of the material and prevents side reactions and erosion.

Benefits of technology

It significantly improves the first-time curum efficiency, discharge specific capacity and cycle stability of the material, delays capacity attenuation, improves rate performance, and can meet the performance needs of actual applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005219445020000141
    Figure BDA0005219445020000141
  • Figure BDA0005219445020000151
    Figure BDA0005219445020000151
Patent Text Reader

Abstract

The present application provides a modified lithium-rich manganese-based positive electrode material and a preparation method thereof, and a battery. The modified lithium-rich manganese-based positive electrode material comprises a core and a shell covering the core, wherein the core comprises a lithium-rich manganese-based positive electrode material, the lithium-rich manganese-based positive electrode material contains K element, and the chemical formula of the lithium-rich manganese-based positive electrode material is Li a K b Ni x Co y Mn z O2, b = 0 ~ 0.18, a = 1.2-b, a + b + x + y + z = 2; the outer shell is titanium oxide, and the titanium oxide includes titanium dioxide. The modified lithium-rich manganese-based positive electrode material can not only further improve the Li + The diffusion rate in the lattice increases Li + Diffusion space improves the material rate performance and capacity retention rate. It can also prevent the active material from contacting the electrolyte, inhibit the loss of oxygen vacancies at the end of the initial charge, and the coating layer is a transition metal oxide, which can enter the lattice of the host material, further improving the stability of the material, thereby improving the material's first coulomb efficiency, discharge specific capacity and cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of lithium-ion batteries, and specifically relates to a modified lithium-rich manganese-based positive electrode material and a preparation method thereof, and a battery. Background Art

[0002] Lithium-ion batteries provide an important guarantee for the development of mobile electronic devices, and have gradually become an important supporting power source for new fields such as electric vehicles and energy storage: the development of lithium-ion batteries with higher energy density has always been the goal pursued by researchers. At present, the energy density of lithium-ion batteries is mainly restricted by the positive electrode materials. Therefore, the development of positive electrode materials with high specific capacity and high voltage is the key to achieving a breakthrough in the energy density of lithium-ion batteries. Lithium-rich manganese-based positive electrode materials are considered to be the most promising next-generation positive electrode materials because of their high specific capacity of more than 250mAh / g, high safety and low cost. However, the performance of lithium-rich manganese-based positive electrode materials still has problems such as fast capacity decay, poor rate performance and cycle voltage decay, which cannot meet the needs of practical applications. Therefore, it is necessary to improve the electrochemical performance of lithium-rich manganese-based positive electrode materials through modification research.

[0003] At present, doping and coating are common methods to improve the first-cycle efficiency, cycle stability and rate performance of lithium-rich manganese-based materials. The mechanism of action is as follows: (1) Form a physical protective barrier to reduce possible side reactions between the positive electrode and the electrolyte. (2) As a hydrogen fluoride (HF) scavenger, it reduces the corrosion of acidic substances in the electrolyte on the electrode material and inhibits the dissolution of transition metal ions in the positive electrode material. (3) Surface modification can also enhance the diffusion rate of Li+ at the interface and improve the rate performance. However, the current modification of lithium-rich manganese-based materials can often only modify one aspect of the lithium-rich manganese-based materials, and cannot modify the performance of multiple aspects of the lithium-rich manganese-based materials at the same time. Therefore, the current modification methods and modification effects cannot meet the current performance requirements for lithium-rich manganese-based positive electrode materials. Summary of the invention

[0004] In order to solve the problems and deficiencies in the prior art, the present application provides a modified lithium-rich manganese-based positive electrode material and a preparation method thereof, and a battery. The modified lithium-rich manganese-based positive electrode material can further improve the Li + The diffusion rate in the lattice increases Li + Diffusion space improves the material rate performance and capacity retention rate. It can also prevent the active material from contacting the electrolyte, inhibit the loss of oxygen vacancies at the end of the initial charge, and the coating layer is a transition metal oxide, which can enter the lattice of the host material, further improving the stability of the material, thereby improving the material's first coulomb efficiency, discharge specific capacity and cycle stability.

[0005] According to the first aspect of the present application, a modified lithium-rich manganese-based positive electrode material is provided, comprising a core and a shell covering the core, wherein the core comprises a lithium-rich manganese-based positive electrode material, the lithium-rich manganese-based positive electrode material contains K element, and the chemical formula of the lithium-rich manganese-based positive electrode material is Li a K b Ni x Co y Mn z O2, b=0-0.18, a=1.2-b, a+b+x+y+z=2; the outer shell is titanium oxide, and the titanium oxide includes titanium dioxide.

[0006] The study found that during the first charge process, when the voltage is charged to around 4.5V, the lattice oxygen will be separated from the material in the form of Li2O. This is an irreversible oxygen escape process, which directly leads to the low first coulomb efficiency of the lithium-rich manganese-based positive electrode material, and the cycle performance of the material will also be affected by this. During the cycle, the migration of metal cations leads to a structural phase change of the material, making it difficult for lithium ions to be embedded again, resulting in a continuous attenuation of the material capacity. In addition to the influencing factors of the intrinsic structure, there are also some external factors that affect the performance of lithium-rich manganese-based positive electrode materials. With the increase in the number of cycles, it is inevitable that the hydrolysis products (HF, CH3OH, etc.) in the electrolyte (mainly lipids) will corrode the positive electrode material. This process will dissolve the transition metal ions and increase the surface electrode / electrolyte interface resistance of the positive electrode material, thereby hindering the diffusion of lithium ions. At the same time, the dissolved transition metal ions will also migrate to the surface of the negative electrode and destroy the SEI film. These adverse effects will directly or indirectly lead to serious attenuation of the capacity and voltage of lithium-rich manganese-based positive electrode materials.

[0007] Therefore, the present application provides a new modified lithium-rich manganese-based positive electrode material, which includes a core and an outer shell, wherein the core includes a lithium-rich manganese-based positive electrode material containing the K element, and in the composition of the core, the introduction of the K element is introduced in the process of preparing the core particles, so that in the core particles, the K element is very uniformly dispersed in the core whose main component is the lithium-rich manganese-based positive electrode material, that is, the bulk phase is uniformly doped, and the K element can exist in the lattice structure of the lithium-rich manganese-based positive electrode material in any way. Specifically, first, K + The radius is slightly larger than Li + Radius, K + Entering the lithium-rich manganese-based structure, Li + Expanded activity space, Li + The diffusion rate in the lattice increases, and the rate performance and capacity retention rate are greatly improved.

[0008] The shell is titanium oxide such as titanium dioxide. TiO2 as a surface coating of lithium-rich manganese-based positive electrode materials is an electrochemically inert substance that prevents active materials from contacting the electrolyte and inhibits the loss of oxygen vacancies at the end of initial charging. At the same time, TiO2 is a transition metal oxide that enters the crystal lattice of the host material, thereby improving the stability of the material. Therefore, TiO2 as a coating layer for lithium-rich manganese-based positive electrode materials can effectively improve the structural stability of the material and reduce the side reactions between the positive electrode and the electrolyte, thereby improving the material's first coulombic efficiency, discharge specific capacity and cycle stability.

[0009] Moreover, the combination of K doping and TiO2 coating can not only give full play to the modification effect of K element and TiO2 on lithium-rich manganese-based positive electrode materials, but also will not affect the original performance of lithium-rich manganese-based positive electrode materials. Therefore, the combination of K doping and TiO2 coating can improve the current deficiencies of lithium-rich manganese-based positive electrode materials in many aspects, and significantly improve the performance of current lithium-rich manganese-based positive electrode materials, such as fast capacity decay, poor rate performance, and cycle voltage decay. It effectively improves the overall electrochemical performance of lithium-rich manganese-based materials in all aspects and can meet the needs of practical applications.

[0010] Preferably, in the modified lithium-rich manganese-based positive electrode material, the molar ratio of K element to Li element is 0.005 to 0.08. Under the above molar ratio of K element to Li element, K element can fully expand Li + Activity space, improve Li + While reducing the diffusion rate in the lattice, it can also stably exist in the lattice structure of the lithium-rich manganese-based positive electrode material, effectively improving the structural stability of the lithium-rich manganese-based positive electrode material, thereby optimizing the material's rate performance, capacity retention rate, cycle stability and other performance aspects.

[0011] Preferably, in the modified lithium-rich manganese-based positive electrode material, the molar ratio of K element to Li element is 0.01 to 0.05.

[0012] Preferably, in the modified lithium-rich manganese-based positive electrode material, the molar ratio of K element to Li element is 0.03.

[0013] Preferably, the mass proportion of the shell in the modified lithium-rich manganese-based positive electrode material is 0.5-3.0%. Controlling the mass proportion of the shell within the above range, that is, controlling the coating amount of titanium oxide within a certain range, can take into account the protection effect of the lithium-rich manganese-based positive electrode material and the electrochemical performance of the material, and further optimize the various aspects of the material. This is because if the coating is too thick, the excessively thick coating layer may hinder the effective transmission of lithium ions, increase the charge transfer resistance, and thus affect the electrochemical properties of the material. In addition, an excessively thick coating layer may also increase the preparation cost and difficulty of the material, which is not conducive to practical application. If the coating is too thin, although the discharge specific capacity of the material can be improved, the excessively thin coating layer may not be able to effectively protect the surface of the material, causing the material to be prone to side reactions when in contact with the electrolyte, thereby affecting the cycle stability and safety of the material. In addition, a coating layer that is too thin may not be sufficient to provide adequate protection, making the material susceptible to erosion by the electrolyte, thereby affecting its overall performance. Therefore, selecting a suitable coating thickness is crucial to optimizing the performance of lithium-rich manganese-based positive electrode materials. Appropriate coating thickness can protect the material surface while maintaining effective lithium ion transmission, thereby improving the electrochemical performance and cycle stability of the material.

[0014] Preferably, the mass proportion of the shell in the modified lithium-rich manganese-based positive electrode material is 1.0%.

[0015] According to a second aspect of the present application, a method for preparing the modified lithium-rich manganese-based positive electrode material is provided, characterized in that it comprises the following steps: S1. preparing an aqueous solution of an acrylic compound, placing a Ni source, a Mn source, a Co source, and a K source in the aqueous solution of the acrylic compound and mixing them uniformly, and then adding a Li source thereto to mix, so as to obtain a first mixed solution; S2. after an inert gas is introduced into the first mixed solution for not less than 10 minutes, an initiator is added thereto to initiate polymerization of the acrylic compound, so as to obtain a second mixed solution; S3. placing the second mixed solution at 70 to After forced air drying at 90°C for 1 to 4 hours, continue to react at 70 to 90°C for 1 to 3 hours, then heat to 130 to 160°C and dry for 8 to 16 hours to obtain a polyacrylate precursor; S4. Keep the polyacrylate precursor at 400 to 600°C for 3 to 8 hours to obtain an oxide precursor; S5. Calcine the oxide precursor at 800 to 1000°C for 12 to 16 hours to obtain core particles; S6. Evenly mix the core particles and titanium oxide, keep them at 650 to 850°C for 3 to 8 hours to obtain a modified lithium-rich manganese-based positive electrode material.

[0016] In the preparation method of the modified lithium-rich manganese-based positive electrode material provided in the present application, in the process of introducing the K source and preparing the lithium-rich manganese-based positive electrode material, the acrylic acid compound is mixed with the K source and other raw materials for preparing the lithium-rich manganese-based positive electrode material, such as Ni source, Mn source, Co source, and Li source, which can be polymerized under the action of an initiator to form a polypropionic acid compound, which can have a certain binding effect on metal cations, making the entire system a uniform and dispersed system, so that the distribution of each element in the obtained product is more uniform, and finally optimizing the performance of the lithium-rich manganese-based positive electrode material. In the present application, a uniformly distributed polyacrylic acid-nitrate system is first formed at a relatively low temperature, and then the organic matter is decomposed by decarboxylation and degradation reactions at a relatively high temperature, and further an oxide precursor with a certain structure is formed. In this way, the obtained lithium-rich manganese-based positive electrode material is free from the influence of organic impurities, so that its material performance is further optimized.

[0017] It should be noted here that in the prior art, the oxide precursor is usually prepared by coprecipitation, specifically, a precipitant is added to the mixed metal salt solution, two or more cations contained in the solution are precipitated together to generate a precipitate mixture or a solid solution precursor, filtered, washed, and thermally decomposed to obtain an oxide precursor. However, the addition of a precipitant in the coprecipitation method may cause the local concentration to be too high, resulting in agglomeration or uneven composition. Moreover, during the precipitation process, when the concentration of the solute in the liquid phase reaches saturation, if there is no concentration in the same phase, no precipitation is produced. Only when the concentration dissolved in the solution exceeds the critical saturation, precipitation can proceed spontaneously.

[0018] The method provided by the present application for preparing oxide precursors is a sol-gel method, in which the diffusion of components is within the nanometer range, and the raw materials can be mixed at the atomic level, so that a lithium-rich manganese-based positive electrode material with high initial capacity and ideal cycle performance can be prepared in the end. In addition, the lithium-rich manganese-based positive electrode material prepared by the sol-gel method also has the characteristics of high purity and high activity. Therefore, the present application introduces acrylic compounds to form polyacrylic compounds through polymerization, which can form a good sol-gel system with metal ions in K source, Ni source, Mn source, Co source, Li source, etc., so that the components are mixed at the nanometer level or atomic level, so that the final lithium-rich manganese-based positive electrode material has better electrochemical properties.

[0019] Moreover, in the above preparation method, after multiple steps of reaction and multiple steps of drying, it is more conducive to removing material impurities, improving structural stability, and optimizing the electrochemical performance of the material. In the process of S2-S3, the solution color of the reaction system gradually changes from purple to turbid and then to purple transparent, and then the volume expands rapidly after drying and releases a large amount of heat, which means that the acrylic compound is polymerizing to form a polymer. Then, in S4, it continues to be kept at 400-600 ° C for 3-8 hours, which can remove organic matter (nitrogen oxides (nitrate decomposes into nitrogen oxides, and some metal salts have nitrates) and polyacrylic acid compounds), reduce organic impurities in the positive electrode material, and avoid affecting the electrochemical performance of the positive electrode material. In S5, the core particles are further calcined at a higher temperature, which is conducive to improving its structural strength and further removing organic impurities such as polyacrylic acid compounds or nitrogen oxides, thereby further improving the various performances of the positive electrode material. In S6, the core particles and titanium oxide are calcined at high temperature for a certain time, so that the titanium oxide is tightly coated on the surface of the core particles, and the titanium oxide effectively plays a modifying role on the lithium-rich manganese-based positive electrode material.

[0020] Preferably, in S1, during the preparation of the acrylic acid compound aqueous solution, the mass ratio of the acrylic acid compound to water is 3 to 5: 1. Preferably, the mass ratio of the acrylic acid compound to water is 4:1.

[0021] Preferably, in S1, Ni source, Mn source, Co source, and K source are placed in a mixed system obtained by an aqueous solution of an acrylic compound, and the molar ratio of metal ions to acrylic compounds is 1:1.5 to 3. Controlling the molar ratio of metal ions to acrylic compounds within the above range can ensure a more appropriate doping amount of acrylic compounds, which is more conducive to the overall performance of the entire system and optimizes the electrochemical performance of the positive electrode material. Preferably, the molar ratio of metal ions to acrylic compounds is 1:2.2.

[0022] Preferably, in S1, the mass ratio of Li source, K source, Ni source, Mn source and Co source is 1.2-k: k: 0.08-0.18: 0.08-0.18: 0.40-0.70, wherein k ranges from 0 to 0.08. Preferably, the molar ratio of Li source, K source, Ni source, Co source and Mn source is 1.2-k: k: 0.13: 0.13: 0.54, wherein k ranges from 0 to 0.08.

[0023] Preferably, in S1 and S2, the acrylic compound includes at least one of acrylic acid, methyl acrylate and methyl methacrylate.

[0024] Preferably, in S1 and S2, the Ni source includes at least one of nickel sulfate, nickel nitrate, and nickel chloride; the Mn source includes at least one of manganese sulfate, manganese nitrate, and manganese chloride; the Co source includes at least one of cobalt sulfate, manganese nitrate, and manganese chloride; the K source includes at least one of potassium bicarbonate and potassium acetate; and the Li source includes at least one of lithium carbonate, lithium sulfate, lithium nitrate, lithium acetate, lithium hydroxide, and lithium bicarbonate.

[0025] Preferably, in S2, the amount of initiator added is calculated based on the mass proportion of the initiator in the first mixed solution being 1.5-3.5%; the initiator includes at least one of (NH4)2S2O8 and Na2S2O8. The above content of initiator can ensure sufficient initiation of acrylic compounds, and will not introduce too much initiator to affect the overall performance of the material. Moreover, initiators such as (NH4)2S2O8 and Na2S2O8 will not introduce new impurities, and the S therein can be removed by water washing.

[0026] Preferably, in S2, the amount of the initiator added is calculated based on the mass proportion of the initiator in the first mixed solution being 2.5%.

[0027] Preferably, the initiator is (NH4)2S2O8.

[0028] Preferably, in S2, the initiator is added dropwise, which can control the polymerization rate of the acrylic acid compound to be slow, avoid undesirable phenomena such as violent polymerization, which may cause the molecular weight of the polyacrylic acid polymer to be unbalanced and unevenly distributed, and deteriorate the electrochemical performance of the positive electrode material.

[0029] Preferably, in S2, the inert gas includes nitrogen.

[0030] Preferably, in S2, a mixing operation is performed while the inert gas is introduced, and the mixing operation includes stirring.

[0031] Preferably, in S2, the time for introducing the inert gas is 20 minutes.

[0032] Preferably, in S2, after the addition of the initiator is completed, the reaction is continued for 8 to 12 minutes. Preferably, after the addition of the initiator is completed, the reaction is continued for 10 minutes.

[0033] Preferably, in S4, the temperature is increased to 400-600°C at 3-7°C / min; in S5, the temperature is increased to 800-1000°C at 3-7°C / min; in S6, the temperature is increased to 650-850°C at 3-7°C / min. S4-S5 use a certain heating rate to control the evaporation rate of water during the calcination process, and avoid problems such as too large or too small heating rate affecting the structural strength of the calcined product and the calcination rate.

[0034] Preferably, in S4, the temperature is increased to 400-600°C at 5°C / min; in S5, the temperature is increased to 800-1000°C at 5°C / min; in S6, the temperature is increased to 650-850°C at 5°C / min.

[0035] Preferably, in S4, the temperature is increased to 450°C at 5°C / min; in S5, the temperature is increased to 925°C at 5°C / min; in S6, the temperature is increased to 750°C at 5°C / min.

[0036] Preferably, in S6, the mass ratio of the core particles to the titanium oxide is 1: 0.005 to 0.03. Within the above range, it is beneficial to control the coating amount of the titanium oxide to avoid the coating amount being too large or too small, thereby failing to fully optimize the electrochemical performance of the positive electrode material.

[0037] According to a third aspect of the present application, a positive electrode sheet is provided, comprising the modified lithium-rich manganese-based positive electrode material or the modified lithium-rich manganese-based positive electrode material prepared by the preparation method of the modified lithium-rich manganese-based positive electrode material.

[0038] According to the fourth aspect of the present application, a battery comprises the modified lithium-rich manganese-based positive electrode material or the modified lithium-rich manganese-based positive electrode material prepared by the preparation method of the modified lithium-rich manganese-based positive electrode material. The battery prepared by using the modified lithium-rich manganese-based positive electrode material provided by the present application has excellent electrochemical properties in many aspects, so the battery also has excellent rate performance, capacity retention rate, first coulomb efficiency, discharge specific capacity and cycle stability and other electrochemical properties. DETAILED DESCRIPTION

[0039] In order to enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only embodiments of a part of the present application, rather than all of the embodiments.

[0040] Example 1

[0041] 1. Preparation of modified lithium-rich manganese-based positive electrode materials

[0042] The modified lithium-rich manganese-based positive electrode material of this embodiment is prepared according to the following steps:

[0043] S1. Prepare an acrylic acid compound aqueous solution, place a Ni source, a Mn source, a Co source, and a K source in the acrylic acid compound aqueous solution and mix them evenly, then add a Li source thereto and mix to obtain a first mixed solution; wherein, in the preparation of the acrylic acid compound aqueous solution, the acrylic acid compound is acrylic acid, and the mass ratio of acrylic acid to water is 4:1; and the molar ratio of metal ions to acrylic acid compounds in the system obtained by placing the Ni source, the Mn source, the Co source, and the K source in the acrylic acid compound aqueous solution is 1:2.2; the mass ratio of the Li source, the K source, the Ni source, the Mn source, and the Co source is 1.165:0.035:0.13:0.13:0.54; and the Li source is LiOH·H2O, the K source is KHCO3, the Ni source is Ni(NO3)2·6H2O, the Mn source is Mn(NO3)2·4H2O, and the Co source is Co(NO3)2·6H2O;

[0044] S2. After nitrogen gas was introduced into the first mixed solution for 20 min, an inert gas was introduced while stirring, and an initiator ((NH4)2S2O8) was added dropwise thereto to initiate polymerization of an acrylic compound (acrylic acid). After the addition of the initiator was completed, the reaction was continued for 10 min to obtain a second mixed solution;

[0045] S3. The second mixed solution was placed in 80°C for 2h under blast drying, and then continued to react at 80°C for 2h, and then the temperature was increased to 140°C at 5°C / min and dried for 12h to obtain a polyacrylate precursor;

[0046] S4. placing the polyacrylate precursor in a muffle furnace, heating the temperature to 450°C at 5°C / min and keeping the temperature for 5h to obtain an oxide precursor;

[0047] S5. The oxide precursor is heated to 925°C at 5°C / min and calcined for 14 hours to obtain a core particle. The chemical formula of the lithium-rich manganese-based positive electrode material in the core particle is Li 1.165 K 0.035 Ni 0.13 Co 0.13 Mn 0.54 O2;

[0048] S6. After the core particles and titanium oxide (titanium dioxide) are evenly mixed, the mass ratio of the core particles to titanium oxide is 1:0.03, placed in a muffle furnace, heated to 750°C at 5°C / min and kept warm for 5 hours to obtain a modified lithium-rich manganese-based positive electrode material. The modified lithium-rich manganese-based positive electrode material includes a core and a shell covering the core, and the core is a lithium-rich manganese-based positive electrode material containing the K element.

[0049] After relevant tests, in the above-mentioned modified lithium-rich manganese-based positive electrode material, the molar ratio of K element to Li element is 0.03, and the mass proportion of the outer shell (titanium dioxide) in the modified lithium-rich manganese-based positive electrode material is 1.0%.

[0050] 2. Preparation of batteries

[0051] ① Preparation of positive electrode sheet: The modified lithium-rich manganese-based positive electrode material, conductive agent 1 (Super P), conductive agent 2 (KS-6), and binder (PVDF) prepared above were added to NMP at a mass ratio of 80:6:6:8 and mixed evenly to obtain positive electrode slurry, and the positive electrode sheet was prepared with the positive electrode slurry obtained. The compaction density of the positive electrode sheet is 3.6g / cm 3 .

[0052] ② Preparation of negative electrode sheet: Graphite, conductive agent (SP), binder 1 (CMC), and binder 2 (SBR) were added into water at a mass ratio of 96.0:0.7:1.3:2.0 and mixed to obtain negative electrode slurry, and a negative electrode sheet was prepared using the obtained negative electrode slurry.

[0053] ③ Use the above-mentioned positive electrode sheet, negative electrode sheet, 1 mol / L LiPF6 / EC+DMC+EMC (v / v=1:1:1) electrolyte, PE+alumina separator, and shell to assemble the soft-pack battery using conventional production processes.

[0054] Example 2

[0055] 1. Preparation of modified lithium-rich manganese-based positive electrode materials

[0056] In the preparation process of the modified lithium-rich manganese-based positive electrode material in this embodiment, the difference from Example 1 is that the mass ratio of the Ni source, Mn source, Co source, K source, and Li source in S1 is adjusted so that the molar ratio of K to Li is 0.005. Specifically, the mass ratio of the Li source, K source, Ni source, Mn source, and Co source is 1.194:0.006:0.13:0.13:0.54; so that the chemical formula of the lithium-rich manganese-based positive electrode material in the core particles in S4 is Li 1.194 K 0.006 Ni 0.13 Co 0.13 Mn 0.54 O2; and in the modified lithium-rich manganese-based positive electrode material, the molar ratio of K element to Li element is 0.005. The rest is consistent with Example 1.

[0057] 2. Preparation of batteries

[0058] The preparation of the battery in this example is consistent with that in Example 1.

[0059] Example 3

[0060] 1. Preparation of modified lithium-rich manganese-based positive electrode materials

[0061] In the preparation process of the modified lithium-rich manganese-based positive electrode material in this embodiment, the difference from Example 1 is that the mass ratio of the Ni source, Mn source, Co source, K source, and Li source in S1 is adjusted so that the molar ratio of K to Li is 0.08. Specifically, the mass ratio of the Li source, K source, Ni source, Mn source, and Co source is 1.112:0.088:0.13:0.13:0.54; so that the chemical formula of the lithium-rich manganese-based positive electrode material in the core particles in S4 is Li 1.112 K 0.088 Ni 0.13 Co 0.13 Mn 0.54 O2. . The rest is consistent with Example 1.

[0062] 2. Preparation of batteries

[0063] The preparation of the battery in this example is consistent with that in Example 1.

[0064] Example 4

[0065] 1. Preparation of modified lithium-rich manganese-based positive electrode materials

[0066] In the preparation process of the modified lithium-rich manganese-based positive electrode material in this embodiment, the difference from Example 1 is that the mass ratio of the Ni source, Mn source, Co source, K source, and Li source in S1 is adjusted so that the molar ratio of K to Li is 0.003. Specifically, the mass ratio of the Li source, K source, Ni source, Mn source, and Co source is 1.1964:0.0036:0.13:0.13:0.54; so that the chemical formula of the lithium-rich manganese-based positive electrode material in the core particles in S4 is Li 1.1964 K 0.0036 Ni 0.13 Co 0.13 Mn 0.54 O2. The rest is consistent with Example 1.

[0067] 2. Preparation of batteries

[0068] The preparation of the battery in this example is consistent with that in Example 1.

[0069] Example 5

[0070] 1. Preparation of modified lithium-rich manganese-based positive electrode materials

[0071] In the preparation process of the modified lithium-rich manganese-based positive electrode material in this embodiment, the difference from Example 1 is that the mass ratio of the Li source, K source, Ni source, Mn source, and Co source in S1 is adjusted so that the molar ratio of K to Li is 0.1. Specifically, the mass ratio of the Ni source, Mn source, Co source, K source, and Li source is 1.09:0.11:0.13:0.13:0.54; so that the chemical formula of the lithium-rich manganese-based positive electrode material in the core particles in S4 is Li 1.094 K 0.11 Ni 0.13 Co 0.13 Mn 0.54 O2. The rest is consistent with Example 1.

[0072] 2. Preparation of batteries

[0073] The preparation of the battery in this example is consistent with that in Example 1.

[0074] Example 6

[0075] 1. Preparation of modified lithium-rich manganese-based positive electrode materials

[0076] In the preparation process of the modified lithium-rich manganese-based positive electrode material in this embodiment, the difference from Example 1 is that the mass ratio of the core particles to the titanium oxide (titanium dioxide) in S6 is adjusted to a specific mass ratio of 1:0.003, so that the mass proportion of the shell (titanium dioxide) in the modified lithium-rich manganese-based positive electrode material is 0.3%. The rest is the same as Example 1.

[0077] 2. Preparation of batteries

[0078] The preparation of the battery in this example is consistent with that in Example 1.

[0079] Example 7

[0080] 1. Preparation of modified lithium-rich manganese-based positive electrode materials

[0081] In the preparation process of the modified lithium-rich manganese-based positive electrode material in this embodiment, the difference from Example 1 is that the mass ratio of the core particles to the titanium oxide (titanium dioxide) in S6 is adjusted to a specific mass ratio of 1:0.02, so that the mass ratio of the shell (titanium dioxide) in the modified lithium-rich manganese-based positive electrode material is 2.0%. The rest is the same as Example 1.

[0082] 2. Preparation of batteries

[0083] The preparation of the battery in this example is consistent with that in Example 1.

[0084] Example 8

[0085] 1. Preparation of modified lithium-rich manganese-based positive electrode materials

[0086] In the preparation process of the modified lithium-rich manganese-based positive electrode material in this embodiment, the difference from Example 1 is that the mass ratio of the core particles to the titanium oxide (titanium dioxide) in S6 is adjusted to 1:0.035, so that the mass ratio of the shell (titanium dioxide) in the modified lithium-rich manganese-based positive electrode material is 3.5%. The rest is the same as Example 1.

[0087] 2. Preparation of batteries

[0088] The preparation of the battery in this example is consistent with that in Example 1.

[0089] Example 9

[0090] 1. Preparation of modified lithium-rich manganese-based positive electrode materials

[0091] In the preparation process of the modified lithium-rich manganese-based positive electrode material in this embodiment, the difference from that in Example 1 is that the molar ratio of metal ions to acrylic acid compounds (acrylic acid) in the system obtained by placing the Ni source, Mn source, Co source, and K source in the acrylic acid compound aqueous solution in S1 is adjusted to a specific molar ratio of 1:4. The rest is consistent with Example 1.

[0092] 2. Preparation of batteries

[0093] The preparation of the battery in this example is consistent with that in Example 1.

[0094] Example 10

[0095] 1. Preparation of modified lithium-rich manganese-based positive electrode materials

[0096] In the preparation process of the modified lithium-rich manganese-based positive electrode material in this embodiment, the difference from that in Example 1 is that the molar ratio of metal ions to acrylic acid compounds (acrylic acid) in the system obtained by placing the Ni source, Mn source, Co source, and K source in the acrylic acid compound aqueous solution in S1 is adjusted to a specific molar ratio of 1:0.5. The rest is the same as in Example 1.

[0097] 2. Preparation of batteries

[0098] The preparation of the battery in this example is consistent with that in Example 1.

[0099] Embodiment 11

[0100] 1. Preparation of modified lithium-rich manganese-based positive electrode materials

[0101] In the preparation process of the modified lithium-rich manganese-based positive electrode material in this embodiment, the difference from that in embodiment 1 is that the initiator in S2 is adjusted to hydrogen peroxide / ferrous sulfate, and the molar ratio of hydrogen peroxide to ferrous sulfate is 1:1. The rest is the same as in embodiment 1.

[0102] 2. Preparation of batteries

[0103] The preparation of the battery in this example is consistent with that in Example 1.

[0104] Comparative Example 1

[0105] 1. Preparation of modified lithium-rich manganese-based positive electrode materials

[0106] In the preparation process of the modified lithium-rich manganese-based positive electrode material in this comparative example, the difference from Example 1 is that no K source is added to S1. The rest is the same as Example 1.

[0107] 2. Preparation of batteries

[0108] The preparation of the battery in this comparative example is consistent with that in Example 1.

[0109] Comparative Example 2

[0110] 1. Preparation of modified lithium-rich manganese-based positive electrode materials

[0111] In the preparation process of the modified lithium-rich manganese-based positive electrode material in this comparative example, the difference from Example 1 is that the operation of S6 is not performed, that is, the coating of TiO2 in S6 is not performed. The rest is consistent with Example 1.

[0112] 2. Preparation of batteries

[0113] The preparation of the battery in this comparative example is consistent with that in Example 1.

[0114] Comparative Example 3

[0115] 1. Preparation of modified lithium-rich manganese-based positive electrode materials

[0116] In the preparation process of the modified lithium-rich manganese-based positive electrode material in this comparative example, the difference from Example 1 is that the K source in S1 is replaced with a Mg source, and the specific Mg source is Mg(HCO3)2, that is, the lithium-rich manganese-based positive electrode material in the core contains Mg element. The rest is the same as Example 1.

[0117] 2. Preparation of batteries

[0118] The preparation of the battery in this comparative example is consistent with that in Example 1.

[0119] Comparative Example 4

[0120] 1. Preparation of modified lithium-rich manganese-based positive electrode materials

[0121] In the preparation process of the modified lithium-rich manganese-based positive electrode material in this comparative example, the difference from Example 1 is that TiO2 is replaced with MgO in S6, that is, the coating of the shell is changed to MgO. The rest is the same as Example 1.

[0122] 2. Preparation of batteries

[0123] The preparation of the battery in this comparative example is consistent with that in Example 1.

[0124] Comparative Example 5

[0125] 1. Preparation of modified lithium-rich manganese-based positive electrode materials

[0126] This comparative example uses a coprecipitation method to prepare a precursor, and the preparation steps are as follows:

[0127] S1. First, prepare a mixed metal salt solution with a concentration of 2 mol / L, wherein the stoichiometric ratio of Ni:Mn:Co is 0.13:0.54:0.13; the Ni source, Mn source, and Co source are Ni(NO3)2·6H2O, Mn(NO3)2·4H2O, and Co(NO3)2·6H2O, respectively; at the same time, prepare a 2 mol / L sodium hydroxide solution as a precipitant required for the coprecipitation reaction; and a 12.5% ​​ammonia solution as a complexing agent required for the experiment;

[0128] S2. The prepared 2 mol / L mixed metal salt solution and 2 mol / L sodium hydroxide solution were added to the reactor at a rate of 2 ml / min and 3.5 ml / min, respectively, and stirred at 60 ° C at a rate of 500 rpm. During the above reaction, 12.5% ​​ammonia water was added as a complexing agent, and the reaction was carried out for 24 hours. After the reaction was completed, the obtained slurry was washed with water and filtered, and dried in a 110 ° C forced air drying oven for 24 hours to obtain a hydroxide precursor; the volume ratio of the mixed metal salt solution, the sodium hydroxide solution, and the 12.5% ​​ammonia water was 2:3.5:1;

[0129] S3. The above hydroxide precursor is mixed with stoichiometric LiOH·H2O and KHCO3; the mass ratio of K source to Li source is 0.035:1.165; after being mixed evenly, the mixture is preheated at 480°C for 5h, and then calcined in air at 900°C for 12h to obtain core particles; the chemical formula of the lithium-rich manganese-based positive electrode material in the core particles is Li 1.165 K 0.035 Ni 0.13 Co 0.13 Mn 0.5 4O2;

[0130] S4. After the above-mentioned core particles and titanium oxide (titanium dioxide) are evenly mixed, the mass ratio of the core particles to titanium oxide is 1:0.03, placed in a muffle furnace, heated to 750°C at 5°C / min and kept warm for 5 hours to obtain a modified lithium-rich manganese-based positive electrode material. The modified lithium-rich manganese-based positive electrode material includes a core and a shell covering the core, and the core is a lithium-rich manganese-based positive electrode material containing the K element.

[0131] After relevant tests, in the above-mentioned modified lithium-rich manganese-based positive electrode material, the molar ratio of K element to Li element is 0.03, and the mass proportion of the outer shell (titanium dioxide) in the modified lithium-rich manganese-based positive electrode material is 1.0%.

[0132] 2. Preparation of batteries

[0133] The preparation of the battery in this comparative example is consistent with that in Example 1.

[0134] Test Case

[0135] 1. Experimental Construction Method

[0136] The batteries obtained in all the above embodiments and comparative examples were tested for the first coulombic efficiency, discharge specific capacity, cycle capacity retention rate, and rate performance. The specific test methods are as follows:

[0137] (1) First coulombic efficiency: After the prepared battery was left to stand for 3 hours, the charge / discharge test was performed on the LAND battery test system with a voltage range of 2.0 to 4.8 V. The charge capacity of the battery at a current of 0.1C was recorded respectively, and the first cycle coulombic efficiency of the battery at a current of 0.1C was calculated. The first cycle coulombic efficiency was calculated as: first cycle discharge capacity / first cycle charge capacity.

[0138] (2) First cycle charge capacity: refer to the record in (1).

[0139] (3) Cycle capacity retention rate and rate performance (discharge capacity at different rates)

[0140] After the prepared battery was left to stand for 3 hours, the charge / discharge test was performed on the LAND battery test system with a voltage range of 2.0 to 4.8 V. The discharge specific capacity of the battery was recorded at 0.1C, 1C, and 5C for 10 cycles. The capacity retention rate of the battery after 100 cycles at a current of 1C was calculated and recorded. The capacity retention rate was calculated as follows: 1C discharge gram capacity in the 100th cycle / 1C first cycle discharge gram capacity.

[0141] 2. Experimental results

[0142] The test results of the first coulombic efficiency, discharge specific capacity, cycle capacity retention rate and rate performance of the batteries obtained in all the above embodiments and comparative examples are shown in Table 1.

[0143] Table 1. Test results of relevant performance of batteries obtained in the embodiments and comparative examples

[0144]

[0145]

[0146] As can be seen from Table 1, the modified lithium-rich manganese-based positive electrode material provided by the present invention effectively improves the electrochemical performance of the positive electrode material by means of K doping combined with TiO2 coating, so that the battery prepared therefrom has excellent electrochemical performance. For details, please refer to Examples 1 to 11.

[0147] In Comparative Example 1, the lithium-rich manganese-based material of the core does not contain K element; in Comparative Example 2, titanium dioxide is not coated; in Comparative Example 3, the doping element of the core is adjusted to Mg; in Comparative Example 4, the coating of the shell is adjusted to magnesium oxide; all of the above reasons have caused the performance of the modified lithium-rich manganese-based positive electrode material to decline, thus causing the first cycle coulomb efficiency, first discharge specific capacity (high rate) and capacity retention rate of the battery prepared therefrom to decline. This shows that K doping and TiO2 coating have a positive improvement effect on the modification of lithium-rich manganese-based positive electrode materials, and the combination of the two can play a certain synergistic effect, which is more conducive to improving the performance of the positive electrode material and the overall performance of the battery.

[0148] In Comparative Example 5, the conventional co-precipitation method was used to prepare the lithium-rich manganese-based positive electrode material, resulting in a decrease in the performance of the final modified lithium-rich manganese-based positive electrode material, which was manifested as a decrease in the rate performance and cycle performance of the battery performance. This shows that the preparation method provided in the present application is more conducive to obtaining a positive electrode material with better performance, and thus can further optimize the performance of the battery.

[0149] Further comparing Example 1 with Examples 2 to 5, firstly, the molar ratios of K to Li in Examples 4 to 5 are not within the range of 0.005 to 0.08, which is not conducive to improving various aspects of battery performance. Therefore, the relevant performance of the batteries in Examples 4 and 5 is slightly worse than that in Examples 1 to 3.

[0150] Comparing Example 1 with Examples 6 to 8, in Examples 6 and 8, the mass proportion of the modified lithium-rich manganese-based positive electrode material in the shell is too small and too large, respectively, which is not conducive to taking into account both the lithium ion transmission efficiency and the effect of blocking the electrolyte, thereby causing the performance of the battery prepared therefrom to be reduced.

[0151] Comparing Example 1 with Examples 9-10, the amount of acrylic acid added in Examples 9 and 10 is too much and too little, respectively; the above reasons all lead to a decrease in battery performance, which shows that controlling the amount of added acrylic acid within a specific range is more conducive to obtaining a positive electrode material with better comprehensive performance, and therefore is more conducive to improving battery performance.

[0152] Comparing Example 1 with Example 11, the initiator used in Example 11 is hydrogen peroxide / ferrous sulfate, which will introduce impurities that are difficult to remove into the positive electrode material, causing the performance of the positive electrode material to decline, and ultimately leading to a decline in the performance of the battery.

[0153] The above embodiments are only used to illustrate the technical solution of the present application rather than to limit the protection scope of the present application. Although the present application is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solution of the present application can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present application.

Claims

1. A modified lithium-rich manganese-based positive electrode material, characterized in that: The invention comprises a core and a shell covering the core, wherein the core comprises a lithium-rich manganese-based positive electrode material, wherein the lithium-rich manganese-based positive electrode material contains K element, and the chemical formula of the lithium-rich manganese-based positive electrode material is Li a K b Ni x Co y Mn z O2, b=0~0.18, a=1.2-b, a+b+x+y+z=2; The shell is titanium oxide, and the titanium oxide includes titanium dioxide.

2. The modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: In the modified lithium-rich manganese-based positive electrode material, the molar ratio of the K element to the Li element is 0.005 to 0.

08.

3. The modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The mass proportion of the shell in the modified lithium-rich manganese-based positive electrode material is 0.5-3.0%.

4. A method for preparing a modified lithium-rich manganese-based positive electrode material according to any one of claims 1 to 3, characterized in that: The steps include: S1. Prepare an aqueous solution of an acrylic compound, place a Ni source, a Mn source, a Co source, and a K source in the aqueous solution of the acrylic compound and mix them uniformly, and then add a Li source thereto to obtain a first mixed solution; S2. After an inert gas is introduced into the first mixed solution for not less than 10 min, an initiator is added thereto to initiate polymerization of the acrylic compound to obtain a second mixed solution; S3. The second mixed solution is placed in 70 to 90 ° C and dried for 1 to 4 hours, and then the reaction is continued at 70 to 90 ° C for 1 to 3 hours, and then the temperature is raised to 130 to 160 ° C and dried for 8 to 16 hours to obtain a polyacrylate precursor; S4. The polyacrylate precursor is placed at 400 to 600° C. for 3 to 8 hours to obtain an oxide precursor; S5. calcining the oxide precursor at 800 to 1000° C. for 12 to 16 hours to obtain core particles; S6. After the core particles and the titanium oxide are uniformly mixed, the mixture is placed at 650-850° C. for 3-8 hours to obtain the modified lithium-rich manganese-based positive electrode material.

5. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 4, characterized in that: In S1, the Ni source, the Mn source, the Co source, and the K source are placed in a mixed system obtained by the aqueous solution of the acrylic compound, and the molar ratio of metal ions to the acrylic compound is 1:1.5-3.

6. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 4, characterized in that: In said S1 and said S2, The acrylic compound includes at least one of acrylic acid, methyl acrylate and methyl methacrylate; The Ni source includes at least one of nickel sulfate, nickel nitrate and nickel chloride; The Mn source includes at least one of manganese sulfate, manganese nitrate and manganese chloride; The Co source includes at least one of cobalt sulfate, manganese nitrate and manganese chloride; The K source includes at least one of potassium bicarbonate and potassium acetate; The Li source includes at least one of lithium carbonate, lithium sulfate, lithium nitrate, lithium acetate, lithium hydroxide, and lithium bicarbonate.

7. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 4, characterized in that: In S2, the amount of the initiator added is calculated based on the mass proportion of the initiator in the first mixed solution being 1.5-3.5%; The initiator includes at least one of (NH4)2S2O8 and Na2S2O8.

8. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 4, characterized in that: In the S6, the mass ratio of the core particles to the titanium oxide is 1:0.005-0.

03.

9. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 4, characterized in that: In S4, the temperature is raised to 400-600° C. at 3-7° C. / min; In S5, the temperature is raised to 800-1000° C. at 3-7° C. / min; In the above S6, the temperature is increased to 650 to 850°C at a rate of 3 to 7°C / min.

10. A battery, characterized in that: It comprises the modified lithium-rich manganese-based positive electrode material as described in any one of claims 1 to 3, or the modified lithium-rich manganese-based positive electrode material prepared by the preparation method of the modified lithium-rich manganese-based positive electrode material as described in any one of claims 4 to 9.

Citation Information

Cited By

  • Lithium-rich manganese-based positive electrode material and preparation method thereof, battery positive electrode and lithium battery

    CN121778793A